Joint Property Distribution from the Perspective of Maqāṣid al-Sharī‘ah: An Analysis of Decision Number 1290/Pdt.G/2021/PA.Pdg at the Padang Religious Court - Syaflin Halim; Endri Yenti; Aguswan Aguswan; Annasaii bin Jamar (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study examines and analyzes the subjective and normative aspects of the distribution of joint property after divorce in Decision Number 1290/Pdt.G/2021/PA.Pdg. The research aims to analyze the legal process and judicial considerations applied in determining the distribution of joint property between the plaintiff and the defendant. The study employs a qualitative approach combining normative juridical analysis and field research. Primary data are obtained through interviews with ex-husband (plaintiff), ex-wife (defendant), the Chief Judge of the Padang Religious Court, and an Islamic family law scholar. Secondary data consist of judicial decisions, statutory regulations, and relevant academic literature. Data are analyzed using Miles and Huberman’s techniques, including data reduction, descriptive narrative presentation, and iterative conclusion drawing. The findings show that the dispute over joint property arises from different interpretations of ownership between the plaintiff and the defendant regarding a house acquired during marriage. Although Article 35 of Law Number 1 of 1974 and Article 97 of the Kompilasi Hukum Islam (KHI) generally recognize equal division of joint property, the court considers the financial contribution of a third party, namely the defendant’s mother. The judge applies the principles of good faith, distributive justice, and recognition of third-party contributions in determining a proportional distribution of the property. From the perspective of maqāṣid al-sharī‘ah, particularly the principle of ḥifẓ al-māl (protection of property), the decision reflects an effort to safeguard legitimate ownership and prevent unjust enrichment while maintaining fairness in family economic relations. These findings imply that integrating statutory law and maqāṣid principles can strengthen substantive justice in resolving joint property disputes in Islamic family law.